IMPLEMENTASI PERATURAN DAERAH NOMOR 02 TAHUN 2011 TENTANG PAJAK AIR TANAH DI KOTA METRO - S. Endang Prasetyawati (KEADILAN PROGRESIF, 2019)
Tax is a potential alternative as a source of state revenue, the tax sector is a veryappropriate choice, in addition to the relatively stable amount, it is also a reflection of theactive participation of the community in financing development. The problem in this researchis how the application of Metro City Regional Regulation Number 02 of 2011 concerningGroundwater Tax. The method used by the normative juridical approach and analysis iscarried out qualitatively. The results showed that the application of Metro City RegulationNumber 02 of 2011 concerning Groundwater Tax in Metro City is currently based on theimplementing regulations as outlined in Mayor Regulation Number 5 of 2011 concerning theimplementation of Metro City Regulation Number 02 of 2011 concerning Groundwater Tax,but in its application in the field has not been implemented optimally. As a suggestion, theMetro City Government should increase the socialization of Regional Regulations onGroundwater Tax in Metro City to the public, especially taxpayers, so that the public knowsthe existence of Regional Regulations, thereby increasing revenue from taxes, especiallyGroundwater Tax.